Prevalence status and associated factors of wrist postural injury in the Chinese occupational population - Chen, Nengzhou; Li, Guanlin; Sun, Xin; Zhang, Meibian; Zhang, Huadong; Ling, Ruijie; Liu, Yiming; Li, Gang; Ren, Zaoliang; Yin, Yan; Shao, Hua; Zhang, Hengdong; et al. (Frontiers in Public Health, 2022)
Objective This study investigated the prevalence of wrist injuries in 15 industries and different types of work in China. Study on the associated factors of wrist injuries provides a scientific basis for prevention and treatment of wrist diseases in occupational workers. Methods A cross-sectional study of musculoskeletal symptoms of related practitioners in 15 industries, including automobile manufacturing, was conducted to retrieve worker demographic information, working wrist posture, and pain conditions. Multivariable binary logistic regression analyses were performed to identify factors associated with work-related musculoskeletal disorders (WMSDs). Results The prevalence of wrist injuries among the study population was 13.2%. Toy manufacturing, animal husbandry, automobile manufacturing, shoe manufacturing, and biopharmaceutical manufacturing had the highest wrist injury rates at 29.1, 19.1, 14.9, 14.9, and 14.0%, respectively. Among the types of jobs, enamel workers (63.0%), butchers (43.6%), combers (32.5%), welders (31.3%), and scaffolders (26.5%) had the highest prevalence rates. Based on the final multivariate logistic regression analysis: female [odds ratios (OR) = 1.24; 95% confidence interval (CI), 1.15–1.35], 6–10 years of service (OR = 1.11; 95% CI, 1.03–1.18), >10 years of service (OR = 1.15; 95% CI, 1.06–1.25), frequent upward and downward flexion in wrist posture at work (OR = 1.81; 95% CI, 1.84–2.11), and frequent wrist placement on the edge of angular objects increased the OR of injury (OR = 1.52; 95% CI, 1.44–1.61). Need to squeeze objects tightly while working (OR = 1.72; 95% CI, 1.57–1.89), prolonged wrist flexion (OR = 1.86; 95% CI, 1.75–1.97), and work hand position above the shoulder for prolonged periods (OR = 1.11; 95% CI, 1.04–1.19) also suggested the relationship between these factors and the higher prevalence of wrist injury in the workers. The associated factor was physical activity (OR = 0.86; 95% CI, 0.80–0.94). Conclusion This study suggested the relationship between these factors and the higher prevalence of wrist injury in the toy manufacturing, animal husbandry, automobile manufacturing, and shoe-making industries, enamel workers, butchers, and combers. And are work types that require special attention. Females, working age, physical activity, and abnormal posture of the wrist were factors significantly associated with WMSDs.